Some results on generalizations of statistical boundedness - Temizsu, Fatih; Et, Mikail (Wiley, 2021)
In this work, the notion of Delta m-statistical boundedness is generalized with respect to alpha-density and lambda-statistical sense. Besides some inclusion theorems regarding the new sequence spaces Delta m(Sb alpha), Delta lambda m(Sb) and Delta lambda m(Sb alpha) are examined.
Keywords: difference sequences; statistical boundedness; statistical convergence